Reconstructing Islamic Law on the Buy Now Pay Later (BNPL) Scheme in the Context of the Sustainable Development Goals (SDGs) - Rahma Nabilah; Muthoifin; Md. Ishaque (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to reconstruct the Buy Now Pay Later (BNPL) scheme from the perspective of Islamic law by integrating the principles of maqāṣid al-sharī'ah and the Sustainable Development Goals (SDGs). The main focus of the research is to offer an alternative BNPL scheme that is not only by sharia principles, but also supports social justice and economic sustainability. Theoretical framework: This research is based on the principles of maqāṣid al-sharī'ah (protection of property, intellect, and justice) associated with the SDGs, especially SDG 1, SDG 8, and SDG 12. Literature review:  The literature review covers classical and contemporary Islamic legal literature, murābaḥah contracts, and BNPL practices in Indonesian fintech. It was found that there is a lack of integration between sharia principles and sustainability aspects in the digital BNPL scheme. Methods: Using a normative qualitative approach through the study of Islamic legal literature and secondary data on BNPL practice, to formulate an alternative sharia model based on the murābaḥah bi al-taqsīṭ contract. Results: The study found that conventional BNPL schemes contain elements of riba, gharar, and contract ambiguity, which can be detrimental to consumers, especially vulnerable groups. As a solution, a BNPL model based on the murābaḥah contract is offered that meets sharia principles and supports the principles of social justice and economic sustainability. Implications: This research promotes the establishment of a fair Islamic digital financial system, protects consumers, and supports sustainable development goals. Novelty: The novelty lies in the proposed integrative framework between Islamic law and the SDGs in responding to the challenges of BNPL services in the fintech era.